Durie family reunion (Raton Range Raton, New Mexico, 1979)
Newspaper Article on the gathering of 85 Durie descendants for a family reunion.
Master list item #: 2
File location is in the Raton File Cabinet
Keywords: McCreight, Ralph; McCreight, Ralph (Mrs.); Smith, Elsie; Duel, Hazel; Durie, Fred; Durie, Ralph; Wiseman, Frank; Wiseman, Alberta; Britt, Helen; McCreight, Margaret; Johnson, Lola Duel; Local History; Biography; Life and Customs; Family; Reunions; Raton, New Mexico; Missouri; Colorado; Texas; Oregon